2015
DOI: 10.1182/blood-2015-05-640979
|View full text |Cite
|
Sign up to set email alerts
|

Current challenges in diagnostic imaging of venous thromboembolism

Abstract: Because the clinical diagnosis of deep-vein thrombosis and pulmonary embolism is nonspecific, integrated diagnostic approaches for patients with suspected venous thromboembolism have been developed over the years, involving both non-invasive bedside tools (clinical decision rules and D-dimer blood tests) for patients with low pretest probability and diagnostic techniques (compression ultrasound for deep-vein thrombosis and computed tomography pulmonary angiography for pulmonary embolism) for those with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…With CT angiography, a contrast dye needs to be injected into the bloodstream, which creates a risk of contrast-induced nephropathy. 13 Other clinical studies 14,15 used transcranial Doppler US to image the restoration of the blood flow. While US is safe, it does not provide any further information regarding the composition and age of the blood clot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With CT angiography, a contrast dye needs to be injected into the bloodstream, which creates a risk of contrast-induced nephropathy. 13 Other clinical studies 14,15 used transcranial Doppler US to image the restoration of the blood flow. While US is safe, it does not provide any further information regarding the composition and age of the blood clot.…”
Section: Introductionmentioning
confidence: 99%
“…While US is safe, it does not provide any further information regarding the composition and age of the blood clot. 13 It has been reported that the thrombolysis efficiency is much higher if sonothrombolysis is accompanied by clot-dissolving drugs such as tissue plasminogen activator (tPA) 16,17 and heparin. 18,19 Based on histopathological evaluation, it has been observed that the composition 20 of the thrombus is diverse.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary embolism (PE) derived from deep vein thrombosis (DVT) can cause severe dyspnea, which increases mortality. [ 1 4 ] Detection of DVT using ultrasonography (US) and computed tomographic venography (CTV) is necessary for prevention of critical PE. [ 1 3 , 5 ] US is the standard method of screening for DVT, but it has several limitations in terms of detection of thrombi.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 4 ] Detection of DVT using ultrasonography (US) and computed tomographic venography (CTV) is necessary for prevention of critical PE. [ 1 3 , 5 ] US is the standard method of screening for DVT, but it has several limitations in terms of detection of thrombi. [ 3 ] CTV is another powerful method for detecting DVT [ 1 , 3 6 ] ; it has several advantages, such as providing objective results more rapidly than US and concurrently revealing additional important organ information, such as pulmonary arterial status.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation